Toxicological evaluation of Lafoensia pacari A. St.-Hil. (Lythraceae) stem bark extract: Acute and subchronic studies in mice (Brazilian Journal of Pharmaceutical Sciences, 2019)
This study evaluated the safety of Lafoensia pacari A. St.-Hil. (Lythraceae) stem bark hydroalcoholic extract (LPE) through acute and subchronic toxicological assessments in mice. In the acute toxicity evaluation, a single 2000 mg/kg oral dose of LPE was administered to mice and clinical observations were conducted for 14 days. For subchronic toxicity, LPE doses (6.25-1000 mg/kg) were administered orally for 28 days and biochemical, hematological, histopathological analyses and renal and liver expression of Ki-67 were carried out. The acute oral toxicity evaluation of LPE showed no toxicity in mice and it was was classified as category 5 (LD50>2000-5000 mg/kg). In a repeated dose 28-day toxicity study, LPE (100-1000 mg/kg) led to an increase in reticulocytes, which suggests a possible proliferative effect on blood cells. In addition, LPE (400-1000 mg/kg) of produced alterations in biochemical parameters, although no microscopic changes were found in the organs analyzed. A normal expression of the Ki-67 cell proliferation indicator was observed in the kidney and liver tissues, which suggests that LPE does not bring about changes in the proliferative activity of these organs. In conclusion, LPE should be used with caution, particularly in larger doses over longer periods and also in combination with other medication.